Hemodynamic deterioration due to increased anterior and posterior cardiac compression during posterior spinal fusion for scoliosis with pectus excavatum. (May 2022) - Adachi, Ryota; Nishihara, Tasuku; Morino, Tadao; Sekiya, Keisuke; Kitamura, Sakiko; Konishi, Amane; Takasaki, Yasushi; Miura, Hiromasa; Abe, Naoki; Yorozuya, Toshihiro
Hemodynamics may deteriorate during the perioperative period when performing posterior spinal fusion in patients with pectus excavatum and scoliosis. A 13-year-old teenager diagnosed with Marfan syndrome had thoracic scoliosis and pectus excavatum. Thoracic scoliosis was convex to the right, and a right ventricular inflow tract stenosis was observed due to compression induced by the depressed sternum. The patient underwent T3–L4 posterior spinal fusion surgery for scoliosis. Deterioration of hemodynamics was observed when the patient was placed in the prone position or when the thoracic spine was corrected to the left front. Postoperative computed tomography examination showed that the mediastinal space was narrowed due to the corrected thoracic spine. Special attention should be paid in the following cases: (1) severe pectus excavatum, (2) right ventricular inflow tract compression due to depressed sternum on the left side, (3) correction of the thoracic spine on the left front, (4) long-term surgery, and (5) risk of massive bleeding. In some cases, pectus excavatum surgery should be prioritized.